Prediction of stress-related gastrointestinal bleeding in patients with aneurysmal subarachnoid hemorrhage using caudate Hounsfield unit value in ASPECT score - Wang, Ke; Yuan, Kexin; Li, Runting; Lin, Fa; Chen, Yu; Yang, Jun; Han, Heze; Li, Tu; Jia, Yitong; Zhou, Yunfan; Zhang, Haibin; Li, Ruinan; et al. (Frontiers in Neurology, 2023)
Background: Stress-related gastrointestinal bleeding (SRGB) is one of the major complications after aneurysmal subarachnoid hemorrhage (aSAH), and it can present challenges in patient care and treatment. The aim of this study was to explore the clinical significance of the caudate HU value in the Alberta Stroke Program Early CT (ASPECT) score for predicting SRGB in patients with aSAH.We retrospectively analyzed the data of 531 aSAH patients admitted to our institution between 2019 and 2022. Potential predictors of SRGB were identified using multivariate Cox regression analysis. We used a restricted cubic spline (RCS) to evaluate whether there is a nonlinear relationship between the right caudate HU value and SRGB. MaxStat analysis was performed to identify the optimal cutoff point for the right caudate HU value. Another Kaplan-Meier method with the log-rank test was used to analyze the right caudate HU value in predicting the occurrence of SRGB.The incidence rate of SRGB was 17.9%. In the multivariate Cox regression analysis, the right caudate HU value was an independent predictor of SRGB (Hazard ratio [HR] = 0.913; 95% confidence interval [CI]: 0.847-0.983, and p = 0.016). The RCS indicated that the incidence of developing SRGB reduces with increasing right caudate HU values (nonlinear p = 0.78). The optimal cut-off value of the right caudate HU was 25.1.Conclusions: Among aSAH patients, lower right caudate HU values indicated a higher risk of developing SRGB. Our findings provide further evidence for the relationship between the gastrointestinal system and the brain.